Gross National Happiness in Bhutan: Is Buddhist Constitutionalism Legitimate in the Age of Secularism? A Post-Colonial View - Norren, Van (Religions, 2023)
Bhutan’s current constitution draws upon the historical dual system of religious-civil governance under the monarchy (previously Abbot-king) embodying the Mahayana Buddhist concept of Boddhisatva-leadership. Bhutan’s democracy includes an executive-military and pluralist religious custodian role for the King who can be abdicated by parliament. It includes Gross National Happiness as spiritual core, which is non-binding law, incorporating many human rights and human values like compassion. The ban on proselytization in the secular constitution should be viewed from a geopolitical post-colonial perspective of the Christian civilization mission and India/China annexation-politics, and Asian definitions of secularism (Royal patronage of religious pluralism). Christians do experience restrictions on congregation. Hindu Nepalese-origin migrants experience(d) citizenship issues due to geopolitical context but can express religion fully. GNH-policy also has certain implementation difficulties and the GNH index indicates declining community values and spirituality in the face of modernist development. Bhutan’s constitution does not fall within the definition of theocracy. The clergy is excluded from the electoral process. The King’s authority is mainly based on moral leadership, popular uncertainty about imported democracy, and is non-absolute but larger than conventional constitutional monarchies. The constitution is more secular than Buddhist in its binding provisions and offers space for non-GNH oriented governments, also in recent practice. Preserving identity and stability is Bhutan’s aim and secularism needs to look at a group approach, apart from individualist approaches. Human rights traditions could acknowledge the cultural-religious roots that inspired them and keep human dignity alive, instead of wanting to remove it from the state altogether and making human rights the new religion.